Jawabanmu

2014-08-03T13:35:30+07:00
A. (x+7)^2
= (x+7)(x+7)
= x^2 + 7x + 7x + 49
= x^2 + 14x + 49

b.(3x-1)^2
= (3x-1)(3x-1)
= 9x^2 - 3x - 3x + 1
= 9x^2 - 6x + 1

c.(2x+9)^2
= (2x+9)(2x+9)
= 4x^2 + 18x + 18x +81
= 4x^2 + 36x + 81
2014-08-03T13:38:49+07:00
A. (x+7)² = (x+7) (x+7)= x² + 7x + 7x +49 = x² + 14x +49
b. (3x-1)² = (3x-1) (3x-1)= 9x² - 3x - 3x +1= 9x² - 9x +1
c. (2x+9)² = (2x+9) (2x+9)= 4x² + 18x + 18x + 81= 4x² + 36x + 81

maaf kalo salah :)
terimakasih atas jawabannya :0
:)
iya sama: :)